Goal Attainment, Goal Striving, and Well-Being During the Transition to Adulthood: A Ten-Year U.S. National Longitudinal Study - Messersmith, Emily E. (New Dir Child Adolesc Dev, 2010)
This study examines the relation between young adults’ goal achievement, continued goal striving over time, and subsequent well-being. Analysis of a longitudinal subsample of a nationally representative U.S. study of 5,693 adolescents as they transition to adulthood revealed that individuals who met their goals had higher well-being, but that the relation between goal completion and well-being varied by goal content. Continued goal striving was related to well-being and maintained domain-specific self-efficacies, whereas goal disengagement was accompanied by declines in domain-specific self-efficacies. Overall, the results suggest that long-term goal striving is beneficial for well-being during the transition to adulthood.